ASSESSING LANGUAGE LEARNING OUTCOMES IN ONLINE ENVIRONMENTS - Lunn , Elizabeth; Verkhovtsova, Olga; Ishchenko, Olga (Studies in Comparative Education, 2025)
The changes taking place in our lives necessitate adaptation in our methods of learning. The online environment became especially relevant due to Russia’s full-scale war in Ukraine, which forced thousands of Ukrainian students to move away to other cities or countries. Many universities in vulnerable locations are unable to continue even remote studies. When offline schooling is not available, distance learning is an answer. Progress in technologies enabled digital broadcasting and the receipt of programmes of study making online learning even more accessible and convenient for everyone. Such technologies are currently increasingly used to bring lectures and teaching materials remote from an institution to students with regular testing of knowledge, which contributes to more effective learning. The authors aim to present an overview of online language testing and assessment. However, this is not about testing for the sake of grading, but about testing that encourages learning. This means that the test tasks should encourage better learning of the material and have a minimal impact on the assessment. The focus is shifted from simple questioning to different kinds of tests that would address individual difficulties, personality traits, attitudes and preferences for the acquisition process. Evaluating the outcomes while learning a foreign language online is not an easy task. During this process the teacher tries to find out whether the learners are meeting language course goals. This study outlines a number of problems related to fraud, lack of reliability, and increased workload for teachers using online teaching.